Union Democracy and the Law in Canada - Lynk, Michael (Just Labour: A Canadian Journal of Work and Society, 2002)
The legal approach in Canada towards the regulation of trade union democracy has sought to balance individual member's rights with respect for the autonomy of unions. While the United States and England have heavily legislated the areas of internal trade union affairs, Canada has enacted relatively few laws in this area. Rather, unions in Canada have enjoyed considerable legal freedom to develop their own democratic practices and culture. The irony of this approach is that it is the Canadian courts, rather than the more experienced and liberal labour relations boards, that are the final legal arbiters over most internal union matters. However, this is slowly changing. Several provinces have recently enacted modest changes that direct their labour boards to hear complaints from union members respecting the fairness of internal hearings. In the absence of extensive statutory regulation, union constitutions and the democratic traditions behind them become significant legal documents